Svante Pääbo’s paleogenomics results in the context of post-academic transformations of modern technoscience (strokes to the portrait of the Nobel laureate in the socio-cultural context) - Cheshko, V. F. (Biophysical Bulletin, 2023)
The studies of Svante Pääbo, Nobel Laureate in Physiology or Medicine in 2022 are analyzed in two aspects: firstly, as the most striking example of the evolutionary transformation of classical science into the so-called post-academic (techno)science and, secondly, as an element of the so-called "biopolitical turn" in the socio-humanitarian and political knowledge of technological civilization and, in particular, in the concept of "civil society".